The effect of lifestyle modification on severity of constipation and quality of life of elders in nursing homes at Ismailia city, Egypt - Hebatallah Nour-Eldein; Hind M. Salama; Abdulmajeed A. Abdulmajeed; Khaled S. Heissam (Wolters Kluwer Medknow Publications, 2014)
Background: Constipation has a significant impact on the quality of life (QOL). Lifestyle modification is widely accepted and recommended by experts as first-line therapy. Aim: This study aimed at using education on lifestyle modification to improve the QOL of the elderly in nursing homes suffering from functional constipation (FC). Materials and Methods: This study was conducted in nursing homes in Ismailia city, Egypt. It involved 23 elderly patients suffering from FC, who were randomly selected according to the sample equation. They fulfilled the inclusion criteria of being ≥60 years age and according to Rome II criteria. Participants completed personal characteristics and lifestyle questionnaire, the Patient Assessment of Constipation Symptom questionnaire (PAC-SYM) to assess the severity of symptoms, and the Patient Assessment of Constipation Quality of Life Questionnaire (PAC-QOL) to assess pre- and post-intervention. The intervention was conducted in three sessions, of 30 min each, 2 weeks apart using group discussions to educate the sample about dietary pattern, fluid intake, regular physical activity, and the use of laxatives. Statistical analysis: Data were analyzed using a statistical package for social sciences (SPSS version 20). Results: The lifestyle modification education on constipation significantly reduced the severity of symptoms as measured by PAC-SYM, including its total score and subscores (P < 0.001). It also improved the QOL of elderly suffering from constipation as measured by PAC-QOL and reduced total scores of dissatisfaction (P = 0.001) with the exception of the psychosocial subscale. It also significantly increased the satisfaction subscale of PAC-SYM (P < 0.001). Conclusion: Education on lifestyle modification leads to an improvement in the severity of the symptoms of constipation and the QOL of the elderly in nursing homes.